Developments in demographic, training and research projects: Aspects of technical cooperation - Department for Economic and Social Information and Policy Analysis Population Division (United Nations, 1995)
The book is based on experiences gained by the United Nations Secretariat in providing technical assistance for the establishment of demographic training and research centres in English-speaking countries in Africa